Estimating regional returns to education in India: A fresh look with pseudo-panel data. (October 2017) - Bhattacharya, Prabir; Sato, Takahiro
This study analyzes the effects of socio-economic factors on the real wage rates for male workers in India over the period 1983–2010. In particular, we examine the role of human capital by estimating the Mincerian wage equation. We construct a regional level pseudo-panel data set for our analysis. Our findings show that while the return to primary education is remarkably high, the returns to other, higher, levels of education are equally remarkably low for all of India taken together, becoming progressively so as the level of education increases. These findings are in contradistinction to those of the other studies on returns to education in India, all of which, however, have relied on cross-sectional data for their analyses. We also find relatively little effects of caste, tribe and religion on real wage rates in India, suggesting that these factors may not be as important as is sometimes believed.